2016
DOI: 10.1002/cbic.201600454
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Templated Synthesis of Perylenediimide Stacks Utilizing Abasic Sites as Binding Pockets and Reactive Sites

Abstract: DNA is considered to be a promising biomolecule as a template and scaffold for arranging and organizing functional molecules on the nanoscale. The construction and evaluation of DNAs containing multiple functional molecules that are useful for optoelectronic devices and sensors has been studied. In this paper we report the efficient incorporation of perylenediimide (PDI) units into DNA by using abasic sites both as binding sites and as reactive sites and the construction of PDI stacks within the DNA structure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 61 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…In particular, the two Por molecules of P2 b are expected to be co‐facially stacked because they are placed adjacently in one strand. Similar stacked structures consisting of functional chromophores such as perylenebisimide derivatives and cyanine dyes have been reported.…”
Section: Resultssupporting
confidence: 66%
“…In particular, the two Por molecules of P2 b are expected to be co‐facially stacked because they are placed adjacently in one strand. Similar stacked structures consisting of functional chromophores such as perylenebisimide derivatives and cyanine dyes have been reported.…”
Section: Resultssupporting
confidence: 66%
“…[3] Li and co-workersr eported the hydrophobic stacking of 2t o5PDIc hromophores connected in head-to-tail fashion in as ingle strand by tetraethyleneglycol linkers. [10,11] Formation of interand intramolecular PDI dimers and oligomers upon duplex and hairpin formation [12,13] or non-covalentb inding of PDI at abasic sites [14] has also been reported. [10,11] Formation of interand intramolecular PDI dimers and oligomers upon duplex and hairpin formation [12,13] or non-covalentb inding of PDI at abasic sites [14] has also been reported.…”
Section: Introductionmentioning
confidence: 94%
“…The chemical structures of the PDI derivatives (PH and PN) and a schematic illustration of site‐specific modification are shown in Figure a and b. The enzymatically generated abasic (AP) sites with uracil‐DNA glycosylase (UDG) were used as the reactive sites for conjugation with PDI (see the Supporting Information) . In short, double‐stranded DNA (dsDNA) possessing a pair of abasic and reduced abasic sites was complexed with PDI derivatives containing amino groups in a buffer solution.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it has been demonstrated that the introduction of substituents to the perylene ring can modulate the electronic states, hydrophobicity, and intermolecular interactions . Due to excellent photochemical properties and electronic functionality, PDI‐modified nucleic acids have been reported . The photochemical properties of PDI can be easily modulated by introducing substituents into the perylene ring, which suggests that the PDI derivatives can be exploited as both fluorophore and quencher molecules .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation